(untitled) (Journal of the Asiatic Society of Bangladesh, Science, 2016)
The present study was designed to investigate the post-harvest quality loss of locally captured Small Indigenous Species (SIS) based on existing marketing system in Sylhet region. A total of 20 fish harvesters, 30 fish handlers (involve in sorting, loading and unloading, transporting, receiving at market), 10 depot owners, 10 auctioneers, 5 aratders was interviewed and 10 markets were visited to collect data about post-harvest activities and marketing of SIS from some areas of Sylhet and Sunamgonj district from July 2015 to December 2015. At harvesting places (100%) fish were the best quality (defect point <2). Fish sold in early market (7am 9 am) were also acceptable (defect point <2 to <3) in terms of quality. After harvesting rough handling (15%), compactness (3%), delay icing (10%), no icing (45%), marketing process (15%) and transportation (7%) lead to loss of a major proportion of total quality. On the basis of defect point average freshness quality of SIS were found <2 at harvesting places, <2 to <3 in landing center, during sorting, <2 to <3 during transportation and <2 to< 4 at market which were results from different activities associated with SIS handling and marketing. J. Asiat. Soc. Bangladesh, Sci. 42(1): 115-125, June 2016